Participatory surveillance reveals marsh deer mortality event during an extraordinary flood in Ibera Wetlands, Argentina - Orozco, María Marcela (2025)
Mortality events of marsh deer (Blastocerus dichotomus) have been historically described in the southern margins of its geographical range. Few documented cases show how environmental changes and pathogens interact to trigger mortality scenarios and reveal their causes. Here, using a participatory surveillance framework, we document the most extensive marsh deer mortality event observed in the last three decades occurring in Ibera ecoregion, Corrientes, Argentina. Local stakeholders monitored marsh deer disease cases or mortality, and upon detection, emergency response teams conducted extensive field studies, documenting 409 dead marsh deer between May and August 2017. Complete postmortem examinations were performed on 16 deer, revealing hepatic fibrosis associates with Fasciola hepatica and multiple parasite infestations in different tissues. Molecular analysis performed on samples from 82 deer identified parasitic and vector-borne microorganisms, including Anaplasma marginale, Theileria cervi, and Trypanosoma spp. High-tick burden and Trypanosoma spp. were significantly associated with deficient body condition. Concurrently, increased precipitation and watershed height significantly expanded flooded areas, with reduced herbaceous cover indicated by land cover analysis. Our findings suggest that prolonged flooding in Ibera played a critical role in the interactions between habitat availability, marsh deer, and parasites. Environmental stressors likely exacerbated the effects of parasitic infections, highlighting the importance of integrating environmental monitoring with wildlife health assessments. Our results contribute to scientific knowledge that provides tools to enhance management efforts focused on protecting the marsh deer population and its critical habitats.